Additional gastrectomy in early-stage gastric cancer after non-curative endoscopic resection: a meta-analysis. (8th March 2019) - Nie, Run-Cong; Yuan, Shu-Qiang; Li, Yuan-Fang; Chen, Shi; Chen, Yong-Ming; Chen, Xiao-Jiang; Chen, Guo-Ming; Zhou, Zhi-Wei; Chen, Ying-Bo
Abstract: Background and objective: The role of additional gastrectomy after non-curative endoscopic resection remains uncertain. The present meta-analysis aimed to explore the risk factors for early-stage gastric-cancer patients after non-curative endoscopic resection and evaluate the efficacy of additional gastrectomy. Methods: Relevant studies that reported additional gastrectomy after non-curative endoscopic resection were comprehensively searched in MedLine, Web of Science and EMBASE. We first investigated the risk factors for residual tumor and lymph-node metastasis after non-curative endoscopic resection and then analysed the survival outcome, including 5-year overall survival (OS) and 5-year disease-free survival, of additional gastrectomy. Results: Twenty-one studies comprising 4870 cases were included in the present study. We found that residual tumor was associated with larger tumor size (>3 cm) (odds ratio [OR] = 2.81, P < 0.001), undifferentiated tumor type (OR = 1.78, P = 0.011) and positive horizontal margin (OR = 9.78, P < 0.001). Lymph-node metastasis was associated with larger tumor size (>3 cm) (OR = 1.73, P < 0.001), elevated tumor type (OR = 1.60, P = 0.035), deeper tumor invasion (>SM1) (OR = 2.68, P < 0.001), lymphatic invasion (OR = 4.65, P < 0.001) and positive vertical margin (OR = 2.30, P < 0.001). Patients who underwent additional gastrectomy had longer 5-year OS (hazard ratio [HR] = 0.34, P < 0.001), 5-year disease-free survival (HR = 0.52, P = 0.001) and 5-year disease-specific survival (HR = 0.50, P < 0.001) than those who did not. Moreover, elderly patients also benefited from additional gastrectomy regarding 5-year OS (HR = 0.41, P = 0.001). Conclusions: Additional gastrectomy with lymph-node dissection might improve the survival of early-stage gastric-cancer patients after non-curative endoscopic resection. However, risk stratification should be performed to avoid excessive treatment.